The effect of stationary rehabilitative cycling after lower extremity musculoskeletal surgical procedures on gross motor related activities of daily living, lower extremity pain and body structure and function outcomes: a systematic review. (14th October 2020) - Cardenas, Analyssa; Nikolopoulos, Marina; Musselman, Kristin; Fehlings, Darcy
Abstract: Background: Stationary cycling offers a unique rehabilitative strategy to engage recovering tissues of the surgical lower extremity, however, cycling is not routinely implemented following all lower extremity surgeries. There is a need to systematically review and summarize the evidence on rehabilitative cycling after lower extremity musculoskeletal surgeries. Objectives: To conduct a systematic review evaluating stationary cycling initiated within three months post-surgery following lower extremity musculoskeletal surgeries to improve gross motor related activities of daily living, lower extremity pain, and body structure and function measures of the operative lower extremity. Methods: Two independent reviewers searched MEDLINE, EMBASE, CINAHL, and Cochrane Reviews databases. Risk of bias was assessed using the Scottish Intercollegiate Guidelines Network (SIGN) criteria. Results: 3758 articles were screened and three were included, two were rated acceptable and one was rated low quality. Cycling was shown to improve gross motor related activities of daily living following total hip arthroplasty and partial meniscectomy, and decrease knee pain following partial meniscectomy. Evidence does not support the use of cycling to improve body structure and function measures. Conclusions: Evidence supports the use of stationary cycling following total hip arthroplasty and partial knee meniscectomy. Further research is required to build the evidence base.